2019
DOI: 10.1002/cncr.32587
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative associations between health insurance and stage of melanoma at diagnosis among nonelderly adults in the United States

Abstract: Background Health insurance plays a critical role in the accessibility to and quality of health care for patients with melanoma in the United States. Current knowledge regarding the association between insurance status and stage of melanoma is limited because few studies to date have simultaneously controlled for factors known to influence the risk of diagnosis of late‐stage melanoma. The current study was conducted to examine the association between health insurance status and stage of melanoma at the time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Considering that graft kidneys are unlikely to affect the patient's skin and Caucasian candidates are more likely to be paired with Caucasian donors in living donor donations, whether Caucasian donors are a risk factor need to be determined by further studies. Generally, lower socioeconomic status is associated with decreased sun protection practices (34)(35)(36), but recipients with private insurance in our study, which usually means greater socioeconomic status, displayed an elevated risk of PTSC, which may be explained by the fact that most private insurance owners are Caucasian. Meanwhile, Caucasians or private insurance owners have a relatively lower risk of mortality, resulting from timely therapy with a shorter delay between diagnosis and definitive surgery (37,38).…”
Section: Discussionmentioning
confidence: 54%
“…Considering that graft kidneys are unlikely to affect the patient's skin and Caucasian candidates are more likely to be paired with Caucasian donors in living donor donations, whether Caucasian donors are a risk factor need to be determined by further studies. Generally, lower socioeconomic status is associated with decreased sun protection practices (34)(35)(36), but recipients with private insurance in our study, which usually means greater socioeconomic status, displayed an elevated risk of PTSC, which may be explained by the fact that most private insurance owners are Caucasian. Meanwhile, Caucasians or private insurance owners have a relatively lower risk of mortality, resulting from timely therapy with a shorter delay between diagnosis and definitive surgery (37,38).…”
Section: Discussionmentioning
confidence: 54%
“…This may have Dermatology Online Journal || Original been influenced by our urban population coming almost entirely from the city of Baltimore, one of the poorest cities with highest crime rates in the United States, possibly masking disparities between rural and urban patients because both groups in the study were disadvantaged [11,12]. A recent study by Abudu et al found that patients with Medicaid or no health insurance were two and three times more likely, respectively, to be diagnosed with late-stage melanoma than those with private insurance [13]. Such findings highlight the impact of socioeconomic factors on melanoma outcomes and it is important to note that both rural and low-income urban communities face barriers to skin cancer care.…”
Section: Discussionmentioning
confidence: 95%
“…11,43 This suggests that having insurance, particularly plans that cover liver-directed therapies or surgical interventions, independently provide survival benefits to patients. 40,99,100 In other malignancies, studies have shown that expansion of public health-insurance options has resulted in a lower percentage of late-stage diagnoses and ultimately improved survival. 101 Enhanced primary care physician visits and screening services for insured patients may also lead to improved patient outcomes due to earlier diagnoses.…”
Section: Strategies To Overcome Individual and Contextual-level Barriers To Care Access To Insurancementioning
confidence: 99%